Pengaruh Gaya Kepemimpinan dan Disiplin terhadap Motivasi Kerja Serta Dampaknya pada Kinerja Pegawai Kecamatan Se Kota Jambi - Mayuhardi Mayuhardi (Universitas Batanghari, 2023)
Leadership style is a behavioral norm that is used by someone when that person influences the behavior of others, the right leadership style and supported by discipline will motivate employees to perform well. The purpose of this study was to examine the effect of leadership style, discipline, work motivation on employee performance. The influence of leadership, discipline, work motivation and employee performance were tested both directly and indirectly. To test the above issues, a direct survey was carried out by distributing questionnaires to District employees throughout Jambi City. Data analysis is done by path analysis. The results of this study indicate that leadership, discipline and work motivation have an effect either simultaneously or partially on employee performance. Leadership style, discipline, work motivation and performance of Jambi City sub-district employees are in the medium category. The analytical tool in this study uses a descriptive method with a verification approach. Where to use a range of scales while verification using path analysis or path analysis. The direct influence of Leadership Style and Discipline together through Work Motivation on Employee Performance is 53.93%, the indirect effect is 28.14%, so the total effect is of 82.07%. so that simultaneously the variables of Leadership Style and Discipline through motivation have a significant influence on employee performance